Hi, can someone please check what i did wrong..

So I know that

$\displaystyle V(x) = M''(0)-(M'(0))^2$

My $\displaystyle M(t)=e^{\mu t + \frac{\sigma^2 t^2}{2}} $

$\displaystyle M'(t) = \mu e^{\mu t} + e^{\sigma^2 t}$

$\displaystyle M'(0) = \mu$

$\displaystyle M''(t) = \mu^2 e^{\mu t} + e^{\mu t} + \sigma^2 e^{\sigma^2 t} $

$\displaystyle M''(0) = \mu^2 + 1 + \sigma^2$

Then

$\displaystyle V(x) = \mu^2 + 1 + \sigma^2 - \mu^2$

$\displaystyle V(x) = 1 + \sigma^2 $

But the answer is supposed to be $\displaystyle V(x) = \sigma^2 $

Can someone please check what i did wrong